KOMUNIKASI KELOMPOK DALAM PEMBERDAYAAN MASYARAKAT KAMPUNG KELBUNG PASCA KONFLIK MADURA-SAMPIT. - Moch. Imron Rosyidi (Jurnal Komunikasi, 2018)
Conflict of Sampit in 2001 between Madura community who lived in Sampit and local community of Sambas has still been being strongly memorized by Madura community until the present time. The culture conflict influenced the Madura who had ever lived in Sampit not only physically but alsoeconomically as most of them lost their occupation. However, Mr. Dairobi and his wife were present as the initiators for the Madura to produce handicrafts from agel rope in order to be empowered to reach the partisipative development. This research aims at finding whether the integration of structure, culture, and agent of change have been appropriate for the needs Kelbung community after the MaduraSampit conflict to explain by group communications studies. In addition, this research was conducted qualitatively with IPA (Interpretative Phenomenological Analysis) as the analysis technique. It is a new analysis including “reading and re-reading” to “looking for patterns across cases” to determine whether the relationship among cases are proper for the focus of this study‒social psychology in communication issue. Mefalopulos development Participatory theory about social change was used as the basis theory to explain the research result. It resulted that among the community, women and children suffered psychological trauma more than the others. Therefore, the concept of social engineering by implementing the handicrafts business was considered as a core of the empowerment activities because it involved women as the main labors, in the group communications studies the function of group haveafford the needs of  group members .